Coordination modes of two flexidentate salicylaldimine ligands derived from N-(3-aminopropyl)morpholine toward zinc and copper - Hisham, N.A.I.; Hadi, H.A.; Ali, Hapipah Mohd; Khaledi, H. (2012)
Two flexidentate Schiff-base ligands condensed from salicylaldehyde or 5-chlorosalicylaldehyde with N-(3-aminopropyl)morpholine were prepared in situ and reacted with Zn(II) and Cu(II) salts. Upon complexation, the Schiff bases underwent deprotonation at hydroxyl to act as mono-anionic ligands. When a ligand : metal ratio of 2 : 1 was applied, the deprotonated Schiff bases coordinated metal ions through phenolate and imine in a square-planar or tetrahedral geometry. In contrast, 5-chlorosalicylaldimine reacted with the metal ions in a 1 : 1 ratio to form complexes wherein morpholine nitrogen also participates in an N,N,O-tridentate coordination mode. The structures of the complexes were characterized by spectroscopic methods and single-crystal X-ray diffraction.